2022
DOI: 10.1098/rspb.2022.1389
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen transmission modes determine contact network structure, altering other pathogen characteristics

Abstract: Pathogen traits can vary greatly and heavily impact the ability of a pathogen to persist in a population. Although this variation is fundamental to disease ecology, little is known about the evolutionary pressures that drive these differences, particularly where they interact with host behaviour. We hypothesized that host behaviours relevant to different transmission routes give rise to differences in contact network structure, constraining the space over which pathogen traits can evolve to maximize fitness. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
50
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 76 publications
1
50
1
Order By: Relevance
“…To test this hypothesis, they collated data on human pathogens, for which transmissibility data are far better and more available than for wildlife pathogens. Two characteristics of transmissibility-infectious period and infection probability-revealed that those that transmit on fluid exchange networks tend to have the longest infectious periods, and those with shorter infectious periods compensate by having moderate to high infection probability.Through this neat and logical series of steps, Collier et al [3] show that, across a wide range of taxa, the structure of animal social networks is somewhat…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…To test this hypothesis, they collated data on human pathogens, for which transmissibility data are far better and more available than for wildlife pathogens. Two characteristics of transmissibility-infectious period and infection probability-revealed that those that transmit on fluid exchange networks tend to have the longest infectious periods, and those with shorter infectious periods compensate by having moderate to high infection probability.Through this neat and logical series of steps, Collier et al [3] show that, across a wide range of taxa, the structure of animal social networks is somewhat…”
mentioning
confidence: 99%
“…Through this neat and logical series of steps, Collier et al [3] show that, across a wide range of taxa, the structure of animal social networks is somewhat…”
mentioning
confidence: 99%
See 3 more Smart Citations